Pendampingan Pembuatan Pojok Baca terhadap Peningkatan Minat Baca Siswa di SDN Tenggulun Kecamatan Solokuro Kabupaten Lamongan - Nashihin, Nashihin; Siswadi, Siswadi; Musbihin, Musbihin; Ishaq, Zamroni (Keris: Journal of Community Engagement, 2024)
The reading corner is an effort to develop students' interest in reading by utilizing the classroom corner as a small library. In other words, the benefits of reading can increase self-development, fulfill intellectual demands, fulfill life interests, increase interest in a field, know real things, open life horizons for children, witness other worlds, the world of thoughts and reflections, and change children. To be charming and feel good to say the least. A reading corner or often also called a reading corner is a room located in the corner of the classroom which is equipped with a collection of books and functions as an extension of the library function. The Reading Corner was created not to compete with the School Library, but rather to help the School Library in fostering a love of reading and reading routines in students. So the books provided in the Reading Corner are tried to be different from those available in the School Library. In order to develop students' interest in reading, Reading Corners in each class have benefits, including: 1) Can stimulate students to be like more of reading and have good thinking power. 2) Bring books closer to students so that students are more interested in reading. 3) Helping the School Library in cultivating a reading routine, when the books that students want to read are not available in the School Library. 4) Can be connected as part of the teacher's learning activities. This assistance uses the PAR (Participatory Action Research) method, which is a research methodology that invites individuals and communities to actively participate by taking part in activities in the field of construction or similar facilities with the knowledge they have. This method was carried out to determine efforts to increase students' reading interest. In its implementation there are several stages, namely Observation and Preparation, Introduction, Training and Assistance in Creating a Reading Corner. Based on the assistance activities for creating reading corners that have been carried out, it can be concluded that all students appear skilled in being creative, both in the form of drawing, editing, choosing words and combining colors to add aesthetic value. reading corner in every class.